Acidentes de trabalho com material biológico notificados em Belo Horizonte de 2008 a 2017 - Julianne Santos Mangualde (2019)
Work accidents with biological materials represent serious risks to professionals at their workplace, due to the possibility of contamination by infectious diseases, and may cause temporary and/or permanent incapacities with physical and/or mental impairment. Although many health professionals working within the hospital environment are exposed to a high degree of occupational hazards, other categories can also be contaminated and report the accident. There is a shortage of systematized data and population-based studies that reflect the Brazilian cities reality. For this reason, the study aims to analyze the characteristics of work accidents with biological material reported in the city of Belo Horizonte. This was a cross-sectional epidemiological study. All the occupational accidents with biological material reported in the SINAN Information System for the period from 2008 to 2017, which corresponded to 9,508 cases, were included. The results showed that 72.51% of the records of occupations of accidents occurred with health professionals and 19% with professionals from other categories (non-health). The reports of percutaneous accidents showed a higher prevalence during the inadequate discard of materials and mucosa during surgical/dental procedures in the uni and multivariate model. In the trend analysis, the proportion of CAT openness among health professionals showed a significant increase compared to other non-health professional categories. There was an improvement in the information record throughout the study years. It is essential that hospital institutions and employers of all professional categories plan actions aimed at implementing safe practices that minimize risk to exposures. In addition, managers need to advised their employees and encourage them to notify it.